UPAYA MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN AQIDAH AKHLAK DI SMPN 31 BANDAR LAMPUNG - saputra, Robby (UNISAN JURNAL, 2024)
Sekolah development plans generally include the formulation of the madrasa's vision, mission, objectives and implementation strategies.. above, the formulation of the problem that the author proposes in this study is to find out the implementation of madrasa-based management in an effort to improve the quality of Islamic religious education learning at Di SMPN 31 Bandar Lampung. This type of research is evaluation research using qualitative research methods. According to Sugiyono, evaluation research is research that aims to compare an event, activity and product with established standards and programs, so that evaluation research serves to explain phenomena. Based on the results of observation interviews, and documentation on the implementation of madrasa-based management in an effort to improve the quality of Islamic religious education learning at Di SMPN 31 Bandar Lampung at the planning stage it is quite good.